Adaptive web-based stress management programs among adults with a cardiovascular disease: A pilot Sequential Multiple Assignment Randomized Trial (SMART). Issue 6 (June 2022) - Lambert, Sylvie D.; Grover, Steven; Laizner, Andrea Maria; McCusker, Jane; Belzile, Eric; Moodie, Erica E.M.; Kayser, John William; Lowensteyn, Ilka; Vallis, Michael; Walker, Mathieu; Da Costa, Deborah; Pilote, Louise; et al.
Abstract: Objective: To assess the feasibility and acceptability of using a Sequential Multiple Assignment Randomized Trial (SMART) to optimize the delivery of a web-based, stress management intervention for patients with a cardiovascular disease (CVD). Methods: 59 patients with a CVD and moderate stress were randomized to a self-directed web-based stress management program (n = 30) or the same intervention plus lay telephone coaching (n = 29). After 6 weeks, non-responders were re-randomized to continue with their initial intervention or switched to motivational interviewing (MI). Feasibility, acceptability, and clinical significance were assessed. Results: SMART procedures were feasible. Attrition rates were almost twice as high in the web-only group than the lay coach group. This might be because of the low satisfaction (47%) in the web-only group. On average, 1.7/5 modules were completed. Effect sizes for stress and quality of life generally exceeded 0.2 (clinical benchmark), except for the group that initially received lay coaching and then switched to MI. Conclusions: Results suggest that a larger trial would be feasible. Issues pertaining to attrition and satisfaction for non-responders need to be addressed. Practice implications: Findings contribute to the evidence on how best to develop and deliver e-Health interventions to maximize their efficacy while remaining cost-effective. Highlights: Using a SMART design was feasible to enhance the clinical significance of a web-based, self-directed stress management intervention. Aspects of acceptability need further consideration before a larger trial is undertaken, particularly among non-responders (e.g., stepping up to lay coaching earlier). Findings provide support for a stepped care model that can be further tested to maximize the efficacy of e-Health interventions while potentially remaining cost-effective.